1983
DOI: 10.1080/00223980.1983.9915424
|View full text |Cite
|
Sign up to set email alerts
|

Moral Judgment in Delinquents and Nondelinquents: RecognitionVersusProduction Measures

Abstract: Juvenile delinquents' (n = 60) and nondelinquents' (n = 73) stages of moral development were compared using both recognition and production measures. Juvenile delinquents were found to score significantly lower than nondelinquents on a production measure of moral judgment (the Sociomoral Reflection Measure). A recognition measure (the Sociomoral Reflection Objective Measure), however, did not discriminate between the two groups in an analysis controlled for significant covariates of age, socioeconomic status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2
2

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 16 publications
0
22
2
2
Order By: Relevance
“…Moreover, delinquents scored way lower than the non-delinquents in terms of the level of ego development indicating that these children have failed in the development of their characters and personalities. Studies have shown that delinquents who lack character development are more likely to be abused by their parents and have lacked the care and discipline which would help them to control their impulses [19,20,21,22]. The family status between the delinquents and nondelinquents did, in fact, shed some light on the background for the test of ego development that was carried out in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, delinquents scored way lower than the non-delinquents in terms of the level of ego development indicating that these children have failed in the development of their characters and personalities. Studies have shown that delinquents who lack character development are more likely to be abused by their parents and have lacked the care and discipline which would help them to control their impulses [19,20,21,22]. The family status between the delinquents and nondelinquents did, in fact, shed some light on the background for the test of ego development that was carried out in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Stage 2 (Blasi, 1980;Campagna & Harter, 1975;Gavaghan et al, 1983;Gregg, Gibbs, & Basinger, 1994;Stams et al, 2006;Trevethan & Walker, 1989). In the current study, the men with IDs had no known history of illegal behaviour, but still had less well developed moral reasoning abilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, many recognition instruments do not measure the developmentally younger stages of moral reasoning (Rest, 1979;Rest, Narvaez, Thoma, & Bebeau, 1999) and their validity is questionable, because in contrast to production instruments, they often do not discriminate reliably between offender and non-offender participants. (Basinger & Gibbs, 1987;Gavaghan, Arnold, & Gibbs, 1983;Gibbs et al, 1984;Stams et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since Blasi' s review, several empirical studies (Gavaghan et al, 1983;Chandler & Moran, 1990;Gregg et al, 1994) and meta-analyses (Nelson et al, 1990;Smetana, 1990) have con® rmed this ® nding. According to Smetana (1990) the results of studies utilising the interview method, as well as the objective questionnaire method, derived from Kohlberg' s theory, are ª overwhelmingly supportiveº of the hypothesised relationship between moral competence and delinquency.…”
Section: Empirical Findings On the Relationship Between Moral Judgemementioning
confidence: 93%